The Effect of PC6 Acupressure Therapy on Emesis Gravidarum in First Trimester Pregnant Women - Ni Made Dewi Satrianingsih; Ni Made Egar Adhiestiani; Putu Ayu Dina Saraswati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Emesis gravidarum is the most common disorder found in pregnant women in the first trimester as much as 50% -90%. Acupressure on the pericardium 6 is considered a key point in reducing the symptoms of emesis gravidarum. This study aimed to determine the effect of PC6 acupressure on emesis gravidarum in first trimester pregnant women. This study conducted at UPTD Puskesmas Mengwi III in 2023 November - December. This research was a Quasy Experiment with a pre-post test with control group design. The sample was 42 people consisting of 21 treatment groups and 21 control groups selected by purposive sampling technique. Data collection used the Rhodes Index Nausea Vomiting and Retching questionnaire, then analysis with Wilcoxon and the Mann Whitney Test. The research results showed that the mean score before intervention in the treatment group was 15.86 and after the intervention it was 6.95 (mild emesis gravidarum). The mean score of pre-test in the control group was 16.76 and the post-test was 13.24 (moderate level of emesis gravidarum). This study showed that there is an influence of PC6 acupressure on emesis gravidarum in fisrt trimester pregnant women (p value=0.001<0.05). It is recommended for pregnant women to continue PC6 acupressure so that the symptoms of emesis gravidarum will decrease or even disappear.